Competency Development Strategy For J&T Express Employees In Koya Barat - Fitriani, Rini; Lentari Rumbiak, Grace Colombine; Tuhumena, Chrisostommi Wirayudha (Green Publisher Indonesia, 2025)
This study aims to analyze the competency development strategy of J&T Express employees in West Koya and identify the factors that influence the development of these competencies. The focus of this research is an effort to improve the quality of human resources in facing operational challenges and increasingly fierce competition in the logistics industry. This study uses a descriptive qualitative approach with purposive sampling techniques on three informants consisting of operational supervisors and storage department employees. The data collection technique was carried out through data interviews using data reduction methods and SWOT analysis with IFAS and EFAS matrices visualized in a cartesian diagram. The results of the study show that J&T Express Koya Barat indicates an aggressive strategy by maximizing internal strength to take advantage of external opportunities. Internal strength to take advantage of external opportunities. The right strategy includes increasing technology-based training, coaching and mentoring, and strengthening operational supervision. Influential internal factors include strength in the form of a wide distribution network and energetic human resources, but constrained by limited training and facilities. External factors include e-commerce growth opportunities and the threat of fierce competition and limited quality human resources.